The Development of Cyber Pedagogy in the Digital Age (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article, cyber pedagogy, which teaches pedagogy through digital technologies, and its development stages and features, which is a requirement of the digital age, is studied.